Ecofriendly Extract of Euphorbia hirta as Corrosion Inhibitor on Mild Steel in Sulphuric Acid Medium - KASTHURI*, P.K.; ARULANANTHAM†, A. (Asian Journal of Chemistry, 2024)
The influence of the addition of acid extract of Euphorbia hirta onthe corrosion of mild steel in 1 M H2SO4 was studied by weight lossmeasurement. The inhibition efficiency increases with extract concentrationand immersion period. The effect of temperature studied indicatedthat inhibition efficiency increased with temperature. The negative valueof the free energy of adsorption indicates spontaneous adsorption. Theinhibitor obeys Temkin adsorption isotherm. The inhibition activityis due to the adsorption of active components which are found in theEuphorbia hirta extract.